Mito, imaginário e sociedade em “Três casas e um rio”, de Dalcídio Jurandir - VALÉRIO, Elaine Pastana (Universidade Federal do Pará, 2012)
This dissertation will address the intersection of the elements: Myth, Imagination and Society in the present work three houses and a river, the author marajoara Dalcídio Jurandir. To do so, will be based on theories from different fields of knowledge such as philosophy, anthropology and literature, which from their differences and agreements, are applied to the analysis of the object of this study, which has a significant body of research to be observed in the construction of the narrative. Since myth and imagination are interdependent and both subordinate to the society, which will be studied from the characters in the novel. However, initially, we attempted to understand the issues in a broader sense, as in works of Vernant, Durand, Bachelard, among others, and therefore applied to the analysis of some mythical narratives present in the novel the author marajoara.